The Ministry of Health, 1919-1929 : ideas and practice in a government department - Stacey, SR (1984)
The subject of the thesis is the Ministry of Health's first decade. The chapters may be separated into three loosely related parts. After an introduction setting out the scope of the study, the first part - composed of two chapters - concerns itself with the Ministry's origins and the early months of its existence. ts departmental antecedents are identified and their administrative cultures defined. The impact of the Report of the Machinery of Government Committee, 1918 (Cd. 9230) on thinking about the Ministry's organisation is assessed. The actual arrangement of the department's permanent staff is dealt with in the second chapter, the latter section of which charts the ways that changes in the department's operation reflect changes in Civil servants' views about their bureaucratic function. Particular attention is paid to the Ministry's first permanent secretary, Sir Robert Morant; to the relations of the lay and administrative classes; and to the attitudes and thinking of Sir Arthur Robinson, Morant's successor. The second part is a political biography of Neville Chamberlain, thrice Minister of Health and from 1924 to 1929 the sixth incumbent. t considers the elements in his family back- ground and in his career that fitted him for this ministerial position; and it examines his work practices and relations with official advisers. The subject of the third part - the last two chapters - is the condition of local government in the 1920s as perceived by various officials and members of government enquiries. It discusses the work of the Royal Commission on Local Government, 1923-29 and the drafting of the Local Government Act of 1929. The thesis is completed by a conclusion and by four appendices. The first two list the Ministers of Health and their principal officials in the interwar period. The others provide details of the careers, hierarchy, and Salary scales of the department's permanent staff. There is an extensive bibliography.